Análisis a los estados financieros de la cooperativa de transporte pesado de carga de volquetes, central Shushufindi, de la provincia de Sucumbíos, durante el periodo 2013 - 2014 - Haro Albarracín, Alexandra Elizabeth (2016)
The thesis entitled "ANALYSIS TO THE FINANCIAL STATEMENTS OF THE COOPERATIVE TRANSPORT HEAVY LOAD dump trucks, CENTRAL Shushufindi OF Sucumbios province during the period 2013 - 2014", it was made in compliance with the prerequisites to obtaining the title of Engineer in Accounting and Auditing, CPA, at the National University of Loja, thus adjusting the current Academic Regime Regulations. Analysis of the Financial Statements of the Cooperative, was made based on the fulfillment of the objectives: an analysis of the financial statements was executed by the comparative study of each of the accounts that make up both the Balance Sheet and the Income Statement during the years 2013 and 2014; likewise the financial indicators that allowed real way to know is applied, the level of financial profitability of the entity; and, finally he managed to deliver a report to the manager of the cooperative, in which conclusions and recommendations are issued based on the work done, in order to improve the profitability levels of the financial entity. In conducting this analysis to the financial statements, the use of methods, techniques and procedures was necessary in the first place, the same that allowed proper collection, tabulation and analysis of information on second claim was assessed financially to the Financial Statements for this purpose the use of evaluation methods as the horizontal method, which allowed us to know over time that have been the most important changes in certain accounts and vertical supply valuable information from each of the accounts that make up became necessary both the Balance Sheet (assets, liabilities and equity) and the Statement of income (income, expenses and profit), during the period examined 2013 and 2014; thirdly the application of financial indicators allowed to know the real way the level of indebtedness, liquidity and profitability both economic and financial of the cooperative and finally fourthly may indicate that managed to make the respective report of the study conducted in was necessary which the respective conclusions and recommendations to improve the economic and financial situation of the same were issued. After completion of the work presented a report on the results of the investigation to the manager of the cooperative Heavy Transport Load Dump, Central Shushufindi, in the province of Sucumbios, in which mainly shows that the cooperative has a acceptable economic and financial profitability during the study period, allowing established in the following years, improving services and increasing its customer base. clear, accurate and timely information about the movement of their income and expenses that are generated daily in the Cooperative and will be of great help to the management of the organization, who were based in the same was obtained, to carry out their trading strategies, investment and financing by making the right decisions to allow use of more effective and efficient economic resources, thus contributing to the development and growth of the cooperative.